Integrating Homoeopathy into Palliative Care: Future Possibilities. - Kumari, Anupama (Homoeopathic Heritage, 2025)
Palliation has often been misunderstood as merely temporary relief of symptoms. In conventional medicine, palliation through opposites (contraria contrariis) suppresses symptoms but frequently results in rebound aggravation. Homoeopathy, as enunciated by Dr. Samuel Hahnemann in the Organon of Medicine (§59), offers a unique form of palliation based on the law of similars (simil-ia similibus curentur). Homoeopathic palliation not only provides compassionate relief in a gentle and enduring manner but also promotes movement of the disease process toward true recovery. This article explores the concept, mechanism, clinical relevance, and contemporary significance of homoeopathic palliation.